Predator and pollinator? An invasive hornet alters the pollination dynamics of a native plant - Rojas-Nossa, Sandra V.; O'Shea-Wheller, Thomas A.; Poidatz, Juliette; Mato, Salustiano; Osborne, Juliet; Garrido, Josefina (Basic and applied ecology, 2023)
Invasive vespids are able to disrupt native species assemblages, modify ecological dynamics, and degrade ecosystem services. However, it is often difficult to quantify such effects within invaded ranges, principally due to the complexity of interactions, and a lack of comparative pre-invasion controls. In this study, we thus examine the effects of an invasive hornet, Vespa velutina, upon native species densities and pollination in a major food plant, Hedera hibernica. Using the highly heterogeneous distribution of V. velutina in a coastal area of the northwestern Iberian Peninsula, we assessed the impact of differing hornet abundance on insect diversity, flower visitation frequency, and predator-prey interactions. We then examined resultant effects upon the pollination success of H. hibernica, in the form of fruit and seed set. Our results demonstrated that in areas with high V. velutina abundance, the floral visitation frequencies and durations of insect pollinators were significantly altered. Effects varied widely across insect families, reflected in the differing predation success rates of V. velutina upon various native pollinators, in tandem with competitive exclusion. Interestingly, V. velutina was itself a frequent floral visitor, becoming the most common nectar forager in areas where it was abundant. In spite of this, H. hibernica reproductive success was significantly degraded in these areas, resulting in reduced seed set. As such, V. velutina appears to have multidirectional effects upon pollination services, first as an insect predator, and second as a nectar competitor and pollinator. Crucially, our findings suggest that V. velutina is an inferior pollinator when compared to the native species that it displaces, resulting in a net reduction in pollination efficacy, and hence reproductive success in H. hibernica. This study thus reveals the profound effects of an invasive vespid on native species through both competitive and predatory interactions.